2023
DOI: 10.1186/s12915-023-01742-8
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling adcyap1 as a protective factor linking pain and nerve regeneration through single-cell RNA sequencing of rat dorsal root ganglion neurons

Qi Chen,
Xi-Yin Zhang,
Yu-Pu Wang
et al.

Abstract: Background Severe peripheral nerve injury (PNI) often leads to significant movement disorders and intractable pain. Therefore, promoting nerve regeneration while avoiding neuropathic pain is crucial for the clinical treatment of PNI patients. However, established animal models for peripheral neuropathy fail to accurately recapitulate the clinical features of PNI. Additionally, researchers usually investigate neuropathic pain and axonal regeneration separately, leaving the intrinsic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The field of biotechnology, encompassing molecular biology, high-throughput sequencing, and bioinformatics, has received increasing attention for its potential to identify new therapeutic targets for various diseases. Chen et al (2023) sequenced single cell RNA of rat dorsal root ganglion neurons and found that adcyap1 can act as a protective factor connecting pain and nerve regeneration. At the same time, Du et al (2023) used single-cell RNA sequencing (scRNA-seq) to identify age-related molecular responses in spinal astrocytes under neuropathic pain and identified four potential age-related genes in the spinal astrocyte population.…”
Section: Discussionmentioning
confidence: 99%
“…The field of biotechnology, encompassing molecular biology, high-throughput sequencing, and bioinformatics, has received increasing attention for its potential to identify new therapeutic targets for various diseases. Chen et al (2023) sequenced single cell RNA of rat dorsal root ganglion neurons and found that adcyap1 can act as a protective factor connecting pain and nerve regeneration. At the same time, Du et al (2023) used single-cell RNA sequencing (scRNA-seq) to identify age-related molecular responses in spinal astrocytes under neuropathic pain and identified four potential age-related genes in the spinal astrocyte population.…”
Section: Discussionmentioning
confidence: 99%